1995
DOI: 10.1074/jbc.270.33.19307
|View full text |Cite
|
Sign up to set email alerts
|

ATP Hydrolysis Is Required for the DnaJ-dependent Activation of DnaK Chaperone for Binding to Both Native and Denatured Protein Substrates

Abstract: Using two independent experimental approaches to monitor protein-protein interactions (enzyme-linked immunosorbent assay and size exclusion high performance liquid chromatography) we describe a general mechanism by which DnaJ modulates the binding of the DnaK chaperone to various native protein substrates, e.g. lambda P, lambda O, delta 32, P1, RepA, as well as permanently denatured alpha-carboxymethylated lactalbumin. The presence of DnaJ promotes the DnaK for efficient DnaK-substrate complex formation. ATP h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 29 publications
2
58
1
Order By: Relevance
“…Because YDJ1 cannot substitute for auxilin, our results do not support a model where DnaJ homologs nonspecifically prime Hsc70 to bind substrates, particularly a model where the DnaJ homolog dissociates from Hsc70 before the substrate binds (31). Rather our results support a model where DnaJ homologs only present specific substrates to Hsc70; perhaps the substrates that bind to them.…”
Section: Resultscontrasting
confidence: 53%
“…Because YDJ1 cannot substitute for auxilin, our results do not support a model where DnaJ homologs nonspecifically prime Hsc70 to bind substrates, particularly a model where the DnaJ homolog dissociates from Hsc70 before the substrate binds (31). Rather our results support a model where DnaJ homologs only present specific substrates to Hsc70; perhaps the substrates that bind to them.…”
Section: Resultscontrasting
confidence: 53%
“…Refolding of denatured proteins required both domains of DnaJ: the J domain, which stimulates the ATPase activity of DnaK (17,22,23), and the binding substrate domain (23,24). Based on these observations, it was proposed that after the initial binding of the substrates to DnaJ, they were transferred to the peptide-binding site of DnaK (9 -11), which was also proposed to be activated by DnaJ for binding client proteins (22,25). More recently, a model has been put forward in which binding of DnaJ and ATP-DnaK to the same polypeptide chain leads to formation of ternary complexes.…”
mentioning
confidence: 99%
“…It has been shown that the simultaneous presence of DnaJ and ATP hydrolysis activates the DnaK protein for binding to different protein substrates (23). In the presence of substoichiometric concentrations of DnaJ and ATP, DnaK changes its own af nity to both denatured and native substrates (23,24).…”
Section: Hsp40 and Atp Hydrolysis Activates Hsp70 For Binding To Diffmentioning
confidence: 99%